Modulation of Brain Activity with Noninvasive Transcranial Direct Current Stimulation (tDCS): Clinical Applications and Safety Concerns - Zhao, Haichao; Qiao, Lei; Fan, Dongqiong; Zhang, Shuyue; Turel, Ofir; Li, Yonghui; Li, Jun; Xue, Gui; Chen, Antao; He, Qinghua (Frontiers in Psychology, 2017)
Transcranial direct current stimulation (tDCS) is a widely-used tool to induce neuroplasticity and modulate cortical function by applying weak direct current over the scalp. In this review, we first introduce the underlying mechanism of action, the brief history from discovery to clinical scientific research, electrode positioning and montages, and parameter setup of tDCS. Then, we review its application in clinical samples including people with drug addiction, major depression disorder, Alzheimer’s disease, as well as in children. This review covers the typical characteristics and the underlying neural mechanisms of tDCS treatment in such studies. This is followed by a discussion of safety, especially when the current intensity is increased or the stimulation duration is prolonged. Given such concerns, we provide detailed suggestions regarding safety procedures for tDCS operation. Lastly, future research directions are discussed. They include foci on the development of multi-tech combination with tDCS such as with TMS and fMRI; long-term behavioral and morphological changes; and more animal research to deepen the understanding of the biological and physiological mechanisms of tDCS stimulation.